Continuity of Housing Expression based on the Elderly Bugis Culture - Sakinah, Putri Nur; Hayati, Arina; Faqih, Muhammad (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 10 No 2 (2023): October 2023DO - 10.24843/JRS.2023.v10.i02.p06, 2023)
Elderly people tend to continue passing down cultural values to the next generation. The Bugis community from South Sulawesi has solid cultural values that relate to rules of life and living called "Siri' na Pesse” . Over time, users' needs and desires for homes change and increase, and subsequently affect the ways the Bugis community perceives its living environments. This research aims to identify aspects and elements that are changed during implementing of the "Siri' na Pesse" conception. This identification is based on the perspective of the elderly group of the Bugis community who live in vernacular houses in Tolitoli, Central Sulawesi. For data collection, this research first distributed questionnaires to get information on concepts applied to the vernacular houses of its participants. However, this method did not provide responses relevant to the research criteria and objective. To seek more detailed information, it was then decided to proceed with participants’ observations and in-depth interviews to find out the extent and reasons for applying “Siri' na Pesse” conception in houses. Study results show that "Siri' na Pesse" conception is applied in some design aspects only, which are mainly in building elements of a vernacular living design. Some conceptions are no longer applied due to participants’ declining understanding of cultural values and conditions surrounding the settlements. Keywords: Buginese; elderly; housing; siri’ na pesse ; values Abstrak Lansia cenderung akan mewariskan nilai budaya kepada generasi berikutnya. Suku Bugis memiliki nilai budaya yang kuat terkait dengan aturan hidup dan berhuni yang disebut "Siri' na Pesse" . Seiring waktu, kebutuhan penghuni semakin bertambah dan berubah, sehingga terjadi perubahan cara pandang masyarakat terhadap lingkungan huniannya. Penelitian ini bertujuan untuk mengungkap aspek dan elemen yang berubah dalam penerapan nilai “Siri’ na Pesse” pada hunian dari perspektif lansia Bugis. Partisipan penelitian adalah masyarakat lansia yang tinggal di hunian vernakular Bugis di Tolitoli, Sulawesi Tengah. Tahap pertama, riset ini menyebarkan kuesioner untuk mendapatkan informasi nilai-nilai yang diterapkan pada bangunan hunian vernakular oleh partisipan. Hasil kuesioner kurang menunjukkan hasil yang sesuai dengan kriteria dan tujuan penelitian sehingga dibutuhkan metode penelitian lanjutan untuk lebih mendetailkan. Kemudian, observasi partisipan dan wawancara mendalam dilakukan untuk mengetahui sejauh mana dan alasan penerapan nilai ”Siri’ na Pesse” pada hunian. Hasil penelitian menunjukkan nilai “Siri’ na Pesse” hanya diterapkan pada sebagian aspek terutama pada elemen bangunan dalam desain hunian vernakular. Beberapa nilai tidak lagi diterapkan karena menurunnya pemahaman terhadap nilai budaya dan kondisi lingkungan permukiman. Kata kunci: Bugis; lansia; nilai budaya; hunian; siri’ na pesse